2011
DOI: 10.1088/0004-637x/740/1/6
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Clustering of Protoplanetary Dust and Planetesimal Formation

Abstract: We study the clustering of inertial particles in turbulent flows and discuss its applications to dust particles in protoplanetary disks. Using numerical simulations, we compute the radial distribution function (RDF), which measures the probability of finding particle pairs at given distances, and the probability density function of the particle concentration. The clustering statistics depend on the Stokes number, St, defined as the ratio of the particle friction timescale, τ p , to the Kolmogorov timescale in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 111 publications
(236 reference statements)
8
109
2
Order By: Relevance
“…The large or integral scale L, which contains the energy in this flow, is thus apparently much larger than the vertical distance of the sensor from the boundary (h = 2 m) and plausibly the same as the longitudinal integral scale given as L = 180 m [2], see also [13], thus L/⌘ ⇡ 10 5 . In cascade applications, it may be more meaningful to assess the scale dependence of p(m) at large scales not in terms of multiples of ⌘ as in [8] and most other work [e.g., 20], but in terms of fractions of L. We will also express scale fractions l/L in terms of cascade bifurcation levels N needed to achieve equidimensional volumes l on a side:…”
Section: Figmentioning
confidence: 99%
“…The large or integral scale L, which contains the energy in this flow, is thus apparently much larger than the vertical distance of the sensor from the boundary (h = 2 m) and plausibly the same as the longitudinal integral scale given as L = 180 m [2], see also [13], thus L/⌘ ⇡ 10 5 . In cascade applications, it may be more meaningful to assess the scale dependence of p(m) at large scales not in terms of multiples of ⌘ as in [8] and most other work [e.g., 20], but in terms of fractions of L. We will also express scale fractions l/L in terms of cascade bifurcation levels N needed to achieve equidimensional volumes l on a side:…”
Section: Figmentioning
confidence: 99%
“…25,26 The interaction between very heavy particles and compressible turbulence has been studied by using the same model as for the incompressible case, i.e., only the Stokes drag is considered. 27,28 The detailed model for particles in a compressible flow has been developed recently. [29][30][31] It has also been shown that for certain particle parameters, the point-particle model can still be used to study the particle-shock interaction.…”
mentioning
confidence: 99%
“…This is indeed the case with small scale turbulent eddies (e.g. Pan et al 2011). But if a vortex rotates slowly enough it can be in a so-called "geostrophic balance", which means that its pressure gradients are compensated by Coriolis forces.…”
Section: Question 1: How Does Nature Overcome the Meter Size Barrier?mentioning
confidence: 60%
“…While this model is highly appealing, it should be understood that it is based on scaling relations to extrapolate results from numerical simulations, which inherently have limited spatial resolution, to the real world, where turbulence eddies span many orders of magnitude in size. As pointed out by Pan et al (2011) these scaling relations might be too optimistic in the above papers, meaning that in reality the probabilities of spontaneous planetesimal formation might be prohibitively low. It is clear, however, that the last word is not said on this topic, and it remains an exciting possibility.…”
Section: Wwwan-journalorgmentioning
confidence: 96%